Oracle database 10g : high availability with RAC, Flashback and Data Guard. - Hart, Matthew, ....-; Jesse, Scott, ....- (New York : McGraw-Hill, 2004)
PART I: Logical Availability 1: Oracle and Availability: Illustrated Downtime Scenarios 2: RDBMS Features for Availability 3: Tuning Your Database for Availability PART II: Real Application Clusters 4: RAC Setup and Configuration 5: Database Administration in a RAC Environment 6: Utility Computing: Applications as Services PART III: Disaster Planning 7: Oracle Data Guard: Surviving the Disaster 8: Backup and Recovery for High-Availability Environments 9: Oracle Flashback: Surviving User-Induced Trauma PART IV: Distributed Database Solutions 10: Oracle Streams for High Availability 11: Oracle Net Configuration for Failover
Keywords: Database systemen; Programmeertalen